2017
DOI: 10.3390/molecules22050688
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Profiles in Flowers of Grape Hyacinth

Abstract: Grape hyacinth (Muscari spp.) is a popular ornamental bulbous perennial famous for its blue flowers. To understand the chemical basis of the rich blue colors in this plant, anthocyanin profiles of six blue flowering grape hyacinths as well as one pink and one white cultivar were determined using high-performance liquid chromatography and mass spectrometry. Along with two known compounds, eight putative anthocyanins were identified in the tepals of grape hyacinth for the first time. The accumulation and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Overall, the biochemical analyses showed that there was a significant increase in pelargonidin glycosides as the petals developed, and such accumulation parallels the increasing orange coloration of the petals during development. In most plants, total anthocyanins content increases with the flower development and reaches its peak just before the buds open [43,44], with a rapid accumulation of anthocyanins in petals at the later stages of their development [45,46]. In order to better understand the relationships among the different anthocyanins detected, we performed a row-directed hierarchical clustering analysis (HCL) (S2 Fig).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the biochemical analyses showed that there was a significant increase in pelargonidin glycosides as the petals developed, and such accumulation parallels the increasing orange coloration of the petals during development. In most plants, total anthocyanins content increases with the flower development and reaches its peak just before the buds open [43,44], with a rapid accumulation of anthocyanins in petals at the later stages of their development [45,46]. In order to better understand the relationships among the different anthocyanins detected, we performed a row-directed hierarchical clustering analysis (HCL) (S2 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Pelargonidin derivatives have been found in different plant species including orange cultivars of Pelargonium where they can account for up to 98% of total anthocyanins [54], Dahlia variabilis [55], magenta flowers of Verbena [56], red-purple flowers of Matthiola incana [57] and Ipomoea purpurea [58], red flowers of Hyacinthus orientalis [40], maroon flowers of Pharbitis nil [59], and white and pink flowers of Muscari spp. [44]. All identified anthocyanin molecules of G .…”
Section: Discussionmentioning
confidence: 99%
“…петунидин-3-Оглюкозид. Цветки M. armeniacum содержат только производные дельфинидина и цианидина [13][14][15].…”
Section: фармацияunclassified
“…Grape hyacinth ( Muscari spp. ), named for its unique grape-like color and shape, is a monocotyledonous ornamental bulbous plant that blossoms in mid-spring [22,23]. Generally, grape hyacinth varieties display a single color, such as white, pink, purple, azure, cobalt, violet, or lavender.…”
Section: Introductionmentioning
confidence: 99%